Penurunan TSS, COD, dan Total Nitrogen Air Lindi dengan Constructed Wetland Menggunakan Melati Air (Echinodorus palaefolius) - Mohammad Mirwan; Thineza Ardea Pramesti (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Leachate is water that comes from waste seepage which carries dissolved and suspended contents from the decomposition waste material dan waste decay. The parameters contained in leachate include temperature, TSS, pH, Dissolved Oxygen, total ammonia, nitrate, iron, sulfate, COD, and BOD. One of the leachate treatments is constructed wetlands. Processing using the constructed wetlands method is a wetland processing system engineered for wastewater treatment which utilizes plants, soil, and microorganisms. This research utilizes water jasmine plants using subsurface flow with a continuous system. In this study varying discharge and sampling time. This research was carried out on a laboratory scale by testing the decrease in concentration on the parameters TSS, COD, and Total-Nitrogen parameters. The sampling time was carried out on the 6th, 8th, 10th, 12th, and 14th days. In this study, the largest TSS results were obtained at a discharge of 5L/day with a sampling time of the 14th day reaching 96,3%. The highest reduction in COD at a discharge of 5L/day on day 14 was 94,4%. The decrease in total nitrogen at 5L/day discharge on the 14th day was 89.64%. The pH and temperature were observed for 14 days of research and obtained an average pH and temperature of 7.9 and 26.77℃. pH and temperature in this study are pH and temperature with the optimal range in constructed wetland processing.